An integrated parity-time symmetric wavelength-tunable single-mode microring laser - Weilin Liu (Nature Portfolio, 2017)
The breaking of parity-time symmetric gain and loss profiles can be used to achieve single-mode lasing in coupled microring resonators. Here, Liuet al. show that this effect can be electrically controlled with a tunable lasing wavelength and strong sidemode suppression.